A Child with Acute Encephalopathy Associated with Quadruple Viral Infection - Nakata, Keiko; Kashiwagi, Mitsuru; Masuda, Midori; Shigehara, Seiji; Oba, Chizu; Murata, Shinya; Kase, Tetsuo; Komano, Jun A. (Frontiers in Pediatrics, 2015)
infection does not always result in AE. The risk factors for developing infantile AE upon such infection remain to be determined. Here we report an infant with AE coinfected with human herpesvirus 6 (HHV-6) and three picornaviruses: coxsackievirus A6 (CVA6), enterovirus D68 (EV-D68), and human parechovirus (HPeV). EV-D68 was vertically transmitted to the infant from his mother. CVA6 and HPeV were likely transmitted to the infant at the nursery school. HHV-6 might have been re-activated in the patient. It remains undetermined which pathogen played the central role in the AE pathogenesis. However, active, simultaneous infection by four viruses likely evoke a cytokine storm, leading to the pathogenesis of AE. Conclusion: Infant cases with active quadruple infection by potentially AE-causing viruses have seldom been reported, partly because systematic nucleic acid-based laboratory tests on picornaviruses are not common. We propose that simultaneous viral infection may serve as a risk factor for the development of AE.